A Tale of Two Perspectives on an Impending Supply Disruption. Issue 1 (January 2016) - Ro, Young K.; Su, Hung‐Chung; Chen, Yi‐Su
Abstract : The topic of buyer–supplier relationships has attracted much attention in the extant supply chain management literature, often from a buyer's perspective. But recently, a number of studies have begun to take a dyadic perspective, acknowledging that both parties in a buyer–supplier relationship may possess divergent perspectives on many issues. Unlike existing dyadic‐view studies that have examined perceptual differences in general, we extend this dyadic‐view stream of the literature and examine perceptual differences in the face of an impending supply disruption event. Using a scenario‐based experiment, our results suggest that suppliers seem to have a greater expectation of both buyer opportunism and relationship continuance than what the buyers actually reported. Our results also indicate that the supplier seems to underestimate the influence of relational norms on relationship continuance more so than the buyer. Also, our results indicate that there is no significant difference between the supplier's and buyer's perceptions of the impact of buyer dependence on opportunism. Our findings suggest that both members of an exchange relationship should carefully manage the expectations and norms with their counterparts, particularly when the relationship might be strained by a supply disruption.